2020
DOI: 10.18502/ijm.v12i5.4598
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance pattern and phylogenetic groups of the uropathogenic Escherichia coli isolates from urinary tract infections in Hamedan, west of Iran

Abstract: Background and Objectives: Escherichia coli is the most common causative agent of urinary tract infections (UTIs) in 90-80% of patients in all age groups. Phylogenetic groups of these bacteria are variable and the most known groups are A, B1, B2 and D. The present study aimed to evaluate the phylogenetic groups of E. coli samples obtained from UTIs and their relation with antibiotic resistance patterns of isolates. Materials and Methods: In this study 113 E. coli isolates were isolated from distinct patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
(23 reference statements)
2
2
0
Order By: Relevance
“…The present findings regarding the prevalence of isolates belonging to phylogroup B1 in the environmental samples are consistent with other findings ( 36 38 ). In addition to phylogroup B1, a reduced prevalence of isolates (E05 and ES11) belonging to the phylogroup E was also observed.…”
Section: Discussionsupporting
confidence: 93%
“…The present findings regarding the prevalence of isolates belonging to phylogroup B1 in the environmental samples are consistent with other findings ( 36 38 ). In addition to phylogroup B1, a reduced prevalence of isolates (E05 and ES11) belonging to the phylogroup E was also observed.…”
Section: Discussionsupporting
confidence: 93%
“…In the present research, the prevalence rate of ampicillin resistance in E. coli was the highest. The observed resistance pattern to ampicillin in E. coli ST131 clones in the current research was consistent with former studies in different provinces of Iran [45,46]. The highest prevalence of ampicillin resistance was found in isolates of patients ≤ 12 years old, and resistance rate to this antibiotic was low in the current study [47].…”
Section: Discussionsupporting
confidence: 91%
“…Based on our comprehensive search, 28 studies with eligibility criteria (Figure 1) were included in the meta-analysis (Ramos et al, 2011;Navidinia et al, 2013;Adib et al, 2014;Alizade et al, 2014a;Alizade et al, 2014b;Hemati et al, 2014;Kazemnia et al, 2014;Derakhshandeh et al, 2015;Iranpour et al, 2015;Rahdar et al, 2015;Salmani et al, 2016;Sohrabi and Zeighami, 2016;Hashemizadeh et al, 2017;Hojabri et al, 2017;Salehzadeh and Zamani, 2018;Bahadori et al, 2019;Farajzadah Sheikh et al, 2019;Norouzian et al, 2019;Shahin et al, 2019;Staji et al, 2019;Bakhtiari et al, 2020;Moez et al, 2020;Ranjbar et al, 2020;Yazdanpour et al, 2020). Of the 28 included studies, 17 and 9 studies reported the prevalence of phylogenic groups from hospitalized and community patients, respectively.…”
Section: Database Search and Characterization Of Studiesmentioning
confidence: 99%